Managerial Skills and the Performance of Small and Medium Enterprises in Eastern Uganda: A Case Study of Small and Medium Enterprises in Industrial Division Mbale City - Braceous Komuhoozi (Uganda Christian University, 2024)
This study examined the effect of managerial skills on the performance of SMEs in the Industrial Division of Mbale City. It aimed to assess the impact of entrepreneurial skills, human resource management, and marketing skills on SME performance. Utilizing a sample of 86 respondents, the research employed both qualitative and quantitative methods to analyze the data. The findings revealed that entrepreneurial skills had a minimal effect on SME performance, with a low R-Square value of 0.009, indicating that only 0.9% of the performance variance could be explained by these skills. Strategic planning and opportunity recognition showed positive correlations with performance, while innovation and adaptability had less significant impacts. Human resource management practices also had a limited effect, with an R-Square value of 0.030, signifying that only 3% of the performance variance was attributed to HRM practices. Recruitment, skill development, and performance management showed weak associations with performance, suggesting a need for more comprehensive strategies. Marketing skills similarly had a minimal direct impact, with an R-Square value of 0.021, explaining only 2.1% of the variance. However, moderate positive correlations were found between marketing skills and job satisfaction and SME performance. In conclusion, the study highlighted that while these managerial skills are crucial, their direct impact on SME performance was limited. It recommended adopting a holistic approach that integrates these skills with other critical factors such as market conditions and resource management to enhance overall performance. Future research should explore additional variables and contextual factors for a more comprehensive understanding of SME performance dynamics.
Ugraduate Research